Cоглашение о международных перевозках скоропортящихся пищевых продуктов и о специальных транспортных средствах, предназначенных для этих перевозок: СПС с поправками от 22 июня 2024 года - United Nations Economic Commission for Europe (United Nations, 2024)
Done at Geneva on 1 September 1970 and entered into force on 21 November 1976, the objectives of the Agreement on the International Carriage of Perishable Foodstuffs and on the Special Equipment to be used for such Carriage (ATP) are to facilitate international transport of perishable foodstuffs and to ensure a high level of preservation of the quality of perishable foodstuffs during their carriage. It applies to the carriage of perishable foodstuffs performed on the territory of at least two Contracting States not only by road, but also by rail and by sea (sea crossings must be less than 150 km long). The ATP is an Agreement between States, and there is no overall enforcing authority.